Sovereignty : Organized Hypocrisy. - Krasner, Stephen D. (Princeton University Press, 2001)
The acceptance of human rights and minority rights, the increasing role of international financial institutions, and globalization have led many observers to question the continued viability of the sovereign state. Here a leading expert challenges this conclusion. Stephen Krasner contends that states have never been as sovereign as some have supposed. Throughout history, rulers have been motivated by a desire to stay in power, not by some abstract adherence to international principles. Organized hypocrisy--the presence of longstanding norms that are frequently violated--has been an enduring at.